'Blunt' biopolitical rebel rule: on weapons and political geography at the edge of the state. (2nd January 2023) - Buscemi, Francesco
ABSTRACT: This article analyzes the ways in which processes of weapons acquisition and armed collectives formation contribute to shape rebel polities – with their populations and attendant political geographies – in frontier spaces. It argues that the acquisition of weapons and the formation of an armed ensemble are shaped by political rationalities and techniques of governing the entanglements between humans and weapons that are diffused throughout society as a whole. Drawing on biopolitical governmentality, I also show that by governing weapons acquisition and the formation of an armed force rebel movements shape the rebel polity's collective identity and political geographies of 'vital' space in frontiers. Harnessing fieldwork-based research to study Ta'ang rebel movements in Myanmar, I find that weapons acquisition and the formation of an armed ensembles have been inflected by govern-mentalities of narcotics eradication and ethnonationality. The article concludes that some forms of rebel rule at the edge of the state in Myanmar can be qualified as 'blunt' following work by anthropologist Elliott Prasse-Freeman. That is to say, rebel rule lacking the governmental apparatuses to intensively know and promote life at aggregate scales still operates massifications and divisions of biological populations and political space via the formation and governing of armed ensembles.